2022
DOI: 10.3390/su14148342
|View full text |Cite
|
Sign up to set email alerts
|

Government Participation in Supply Chain Low-Carbon Technology R&D and Green Marketing Strategy Optimization

Abstract: This paper uses the differential game approach to construct a model of cooperative emission reduction involving the government, manufacturing firms, and retail firms under different power structures. It is found that the dominant player receives more subsidies; the development of a mechanism for horizontal technology R&D among enterprises can reduce the financial pressure on the government to implement compensation strategies and improve the effectiveness and performance of supply chain emission reduction;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…Some scholars have also investigated the government's influence on the green supply chain. Li et al [24] established a model of cooperative emission reduction involving the government, manufacturer, and retailer under different power structures. They found that the government can develop differentiated subsidy schemes to achieve Pareto optimality based on different game strategies and revenue-sharing agreements by enterprises.…”
Section: Related Literature 21 Research On Green Supply Chainmentioning
confidence: 99%
“…Some scholars have also investigated the government's influence on the green supply chain. Li et al [24] established a model of cooperative emission reduction involving the government, manufacturer, and retailer under different power structures. They found that the government can develop differentiated subsidy schemes to achieve Pareto optimality based on different game strategies and revenue-sharing agreements by enterprises.…”
Section: Related Literature 21 Research On Green Supply Chainmentioning
confidence: 99%
“…Guo et al [ 36 ] established models for multiple recycling structures to identify the optimal emission reduction strategy of manufacturers. Li et al [ 37 ] studied government participation in supply chain low-carbon technology R&D. It was found that the development of a mechanism for horizontal technology R&D among enterprises can reduce the financial pressure on the government to implement compensation strategies and improve the effectiveness and performance of supply chain emission reduction. Cheng and Zhang [ 38 ] studied the problem of emission reduction technology selection in a green supply chain composed of a single manufacturer and a single retailer through game theory, and further discussed the impact of penalty sharing contract on green supply chain decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As industry decarbonization is often linked to government actions, some studies further consider government actions such as subsidies [46,65], participation [66], etc. In addition, some scholars have also studied the perspective of firms in their research.…”
Section: Low-carbon Dual-channel Supply Chainmentioning
confidence: 99%